Fog water collection and reforestation at a mountain location in a western Mediterranean basin region: air-mass origins and synoptic analysis - Valiente, José A.; Estrela, María J.; Corell, David; Fuentes, David; Valdecantos, Alejandro; Baeza, Manuel J. (ERDKUNDE, 2011)
An inland mountainous location in eastern Spain was selected for reforestation studies based on the fog water collection potential prevailing in the area and the high level of land degradation resulting from recurrent forest fires in the past. Bulk fog-water catches were stored and used in a micro-irrigation network to provide summer emergency water pulses to a plot of reforestation seedlings. Results indicate that survival rates and seedling growth of the two species planted, Pinus pinaster and Quercus ilex, improved with the use of small timely waterings and additional treatments with composted biosolids. Fog collection measurements during the 3-year period of the experiment revealed an average water yield of 3.2 l/m2/day, which, although moderate, is a suitable value for afforestation activities. Fog formation is explained in terms of air mass origin and pathway, atmospheric conditions and orographic features. Statistical analysis of the winds bearing fog and the periodicity of fog collection provide the particular characteristics of the experimental site.